2005
DOI: 10.1074/jbc.m414314200
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Role of Asp-120(81) of Metallo-β-lactamase (IMP-1) by Site-directed Mutagenesis, Kinetic Studies, and X-ray Crystallography

Abstract: Metallo-␤-lactamase IMP-1 is a di-Zn(II) metalloenzyme that efficiently hydrolyzes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
81
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 48 publications
6
81
0
Order By: Relevance
“…Several mutants of Asp120 in the class B3 MBL enzyme L1 from Stenotrophomonas maltophilia showed a 10-to 1,000-fold decrease in k cat compared to wild-type L1, and thus, Asp120 was confirmed to play a significant role in the hydrolysis reaction (22,23). This has also been shown for IMP-1 (24), CphA (25), and BcII (26). To study the role and importance of Asp120 in VIM-7 for zinc binding, thermostability, and catalysis, a D120A mutant was created and analyzed.…”
mentioning
confidence: 50%
“…Several mutants of Asp120 in the class B3 MBL enzyme L1 from Stenotrophomonas maltophilia showed a 10-to 1,000-fold decrease in k cat compared to wild-type L1, and thus, Asp120 was confirmed to play a significant role in the hydrolysis reaction (22,23). This has also been shown for IMP-1 (24), CphA (25), and BcII (26). To study the role and importance of Asp120 in VIM-7 for zinc binding, thermostability, and catalysis, a D120A mutant was created and analyzed.…”
mentioning
confidence: 50%
“…The value of the stereochemical parameter (37), which could discriminate between a square pyramid ( ϭ 0) and trigonal bipyramid ( ϭ 1), is 0.37 { ϭ (34). It must be pointed out that one of the carboxylate oxygen atoms of D120[76] is also involved in hydrogen bonding to the bridging hydroxide oxygen atom (Wat1), suggesting that D120[76] may be particularly important not only in orientating an OH Ϫ acting as a nucleophile to the carbonyl carbon on the ␤-lactam ring but also in positioning the Zn2 and H263 [215], as seen also in the subclass B1 and B3 MBLs (38)(39)(40). These results suggested that SMB-1 has the ability to keep the coordination geometry closer to the transition state through distortion of the regular geometry.…”
Section: Resultsmentioning
confidence: 99%
“…9-14 Bacteroides fragilis (CcrA), 15-17 Elizabethkingia meningoseptica (BlaB), 18,19 as well as the transferable VIM, IMP, SPM and GIM-type enzymes. [20][21][22][23][24][25][26] includes the CphA and imiS lactamases from Aeromonas species. 27-29 Subclass B3, along with the extensively characterized enzyme L1 from Stenotrophomonas maltophilia ,30-33 includes enzymes from environmental bacteria, such as CAU-1 from Caulobacter crescentus 34 and THIN-B from Janthinobacterium lividum , 35 and from opportunistic pathogens like FEZ-1 from Legionella gormanii ,36-38 and GOB from E. meningoseptica.…”
Section: Introductionmentioning
confidence: 99%